Impact of Teleworking on Work‐Related and Home‐Related Stress at During the First Global Lockdown–The International COVISTRESS Study - Sébastien Couarraze; Guillaume Decormeille; Louis Delamarre; Fouad Marhar; Karen Gbaglo; Raimundo Avilès Dorlhiac; Mickael Berthon; Andy Su‐I Liu; Samuel Antunes; Bruno Pereira; Julien S Baker; Morteza Charkhabi; et al. (Brain and Behavior, 2025)
ABSTRACT Background The initial lockdown during the pandemic of COVID‐19 led to adjustments in working conditions, including extensive use of telecommuting whenever possible, putatively influencing both work‐related and home‐related stress. Objectives Our aim was to measure the impact of teleworking on work‐related and home‐related during the COVID‐19 pandemic. Methods The international study was conducted using an online questionnaire to collect demographic and stress‐related data from individuals worldwide during the 2020 pandemic year. Work‐related and home‐related stress levels were evaluated using an uncalibrated visual analog scale, with a range from 0 (none) to 100 (maximum). Results A total of 13,537 individuals from 44 countries completed the survey between January and June 2020. A total of 7356 individuals were engaged in professional activities. Of these, 6639 continued to work, of which 2573 carried on as usual and 4066 teleworked. The teleworkers demonstrated a considerably (p < 0.001) lower level of work‐related stress (58 ± 31.6) in comparison to those who maintained their usual work schedule (63.6 ± 31.1). However, there was no statistically significant variation in home‐related stress between the two groups. The risk of high levels of work‐related stress (stress > 80) was multiplied by 1.76 in women (1.54 to 2.01; p < 0.001), by 1.43 (1.27 to 1.61; p < 0.001) for those who did not telework, by 5.31 (4.57 to 6.18; p < 0.001) for those with high levels of home‐related stress (stress > 80), and by 1.46 (1.22 to 1.76; p < 0.001) for those from continents outside Europe. Home‐related stress is also a risk factor for work‐related stress, and vice versa. Sociodemographic risk factors for higher levels of home‐related stress were age < 50 years old, women, working < 50 h per week, continents outside Europe, and not teleworking were no longer risk factors. Conclusion Telework emerged as a viable option during the initial phase of the global pandemic. This mode of work was associated with lower levels of work‐related stress compared to workers who were required to work in a conventional manner. In terms of home‐related stress, telecommuters experienced more stress than those who continued to work as usual.